The Effect of Azolla microphylla Biomass on Physical Parameter of Peat Water on Siamese Catfish (Pangasianodon hypophthalmus) Rearing Media - Aprilia Dwiningtias; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Peat water has unfavorable physical properties for fishery activities such as high TDS, TSS and turbidity values so that the utilization and management of peatlands is still less than optimal. Efforts to improve the physical parameters of peat water can be done by utilizing the aquatic plant Azolla microphylla as a biofilter that can absorb organic matter. This research was carried out in August-September 2021 at the Experimental Pool and Marine Chemistry Laboratory, Faculty of Fisheries and Marine Affairs, Riau University. The purpose of this study was to determine the effect of Azolla microphylla biomass and to obtain the best biomass in improving the physical parameters of peat water in Siamese catfish (Pangasianodon hypophthalmus) rearing media. This research method used a 1-factor completely randomized design (CRD) with 4 treatment levels and 3 replications (Sudjana, 1991). The parameters measured in this study were TSS using the gravimetric measurement method, TDS using electrometry, turbidity using the nephelometric measurement method, fish length using the formula according to Zonneveld (1991) and feed conversion using the formula according to Effendie (1997). The treatments in this study were the administration of different Azolla microphylla biomass, namely Am0 (Control), Am1 (20g/m2), Am2 (40g/m2) and Am3 (60g/m2). The results showed that the best treatment was by giving 60 g/m2 of biomass because it was able to improve the physical parameters of peat water for catfish rearing media such as reducing TSS by 68.5% (83.67 mg/l – 26.33 mg/l), TDS of 37.65% (131 mg/l – 81.67 mg/l) and turbidity of 70.5% (52.51 NTU – 15.47 NTU). The absolute length of the fish was 2.50 cm and the feed conversion was 1.14. The Student-Newman-Keuls test showed that azolla had an effect on reducing the levels of TSS, TDS and turbidity of peat water in siamese catfish rearing media.